2018
DOI: 10.1111/febs.14680
|View full text |Cite
|
Sign up to set email alerts
|

MAGP‐1 and fibronectin control EGFL7 functions by driving its deposition into distinct endothelial extracellular matrix locations

Abstract: The extracellular matrix (ECM) is essential to provide mechanical support to tissues but is also a bioactive edifice which controls cell behavior. Cell signaling generated by ECM components through integrin‐mediated contacts, modulates cell biological activity. In addition, by sequestrating or releasing growth factors, the ECM is an active player of physiological and pathological processes such as vascular development. EGFL7 is mainly expressed during blood vessel development and is deposited in the ECM after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…2b). Interestingly, these C3 cells expressed high levels of extracellular matrix transcripts implicated in cell migration, including fibronectin (FN1), periostin (POSTN), epidermal growth factor-like domain multiple 7 (EGFL7) 17,18 , and agrin (AGRN) [19][20][21][22] ( Supplementary Fig. 3b, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2b). Interestingly, these C3 cells expressed high levels of extracellular matrix transcripts implicated in cell migration, including fibronectin (FN1), periostin (POSTN), epidermal growth factor-like domain multiple 7 (EGFL7) 17,18 , and agrin (AGRN) [19][20][21][22] ( Supplementary Fig. 3b, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, MFAP2 deficient mice exhibited progressive osteopenia, accompanied by increased osteoclast formation and elevated receptor activator of NF-kB ligand (RANKL) expression (Craft et al, 2012). In line with this, mice with conditional knockout of MFAP2 was found to promote the deposition of EGFL7 into fibres in endothelial ECM, which is important for vascular development (Villain et al, 2018).…”
Section: Molecular Structure Of Mfap Family Proteinsmentioning
confidence: 87%
“…Fibrillin-containing microfibrils are particularly important in modulating TGF␤ signaling and the mechanisms whereby microfibril-associated proteins regulate growth factor availability and activity are complex. We and others have shown that the fibrillin-binding partners MAGP-1 and MAGP-2 work together with fibrillin to modulate TGF␤ availability in the ECM (16,(27)(28)(29). Mutations in MAGP genes lead to phenotypes in mice and humans that are associated with abnormal growth factor signaling (15, 16, 18, 30 -33).…”
Section: Discussionmentioning
confidence: 99%